Deep Vadose Zone Respiration Contributions to Carbon Dioxide Fluxes from a Semiarid Floodplain. Issue 7 (28th July 2016) - Tokunaga, Tetsu K.; Kim, Yongman; Conrad, Mark E.; Bill, Markus; Hobson, Chad; Williams, Kenneth H.; Dong, Wenming; Wan, Jiamin; Robbins, Mark J.; Long, Philip E.; Faybishenko, Boris; Christensen, John N.; et al.
Abstract : Core Ideas: A significant fraction of CO2 fluxes from a semiarid floodplain originates from below the root zone. Measured and calculated field CO2 fluxes are consistent. Laboratory‐measured respiration rates are consistent with field results. Although CO2 fluxes from soils are often assumed to originate within shallow soil horizons (<1‐m depth), relatively little is known about respiration rates at greater depths. We compared measured and calculated CO2 fluxes at the Rifle floodplain along the Colorado River and measured CO2 production rates of floodplain sediments to determine the relative importance of deeper vadose zone respiration. Calculations based on measured CO2 gradients and estimated effective diffusion coefficients yielded fluxes that are generally consistent with measurements obtained at the soil surface (326 g C m −2 yr −1 ). Carbon dioxide production from the 2.0‐ to 3.5‐m depth interval was calculated to contribute 17% of the total floodplain respiration, with rates that were larger than some parts of the shallower vadose zone and underlying aquifer. Microbial respiration rates determined from laboratory incubation tests of the sediments support this conclusion. The deeper unsaturated zone typically maintains intermediate water and air saturations, lacks extreme temperatures and salinities, and is annually resupplied with organic carbon from snowmelt‐driven recharge and by water table decline. This combination of favorable conditions supports deeper unsaturated zone microbial respiration throughout the year.